Maintaining social and emotional wellbeing among older adults during periods of increased social isolation: lessons from the COVID-19 pandemic - Brigitta Scarfe; Claire Adams; Eyal Gringart; Daniel McAullay; Moira Sim; Natalie Strobel (Australian Journal of Psychology, 2022)
Objective Older adults are vulnerable to isolation and poor emotional wellbeing during COVID-19, however, their access to appropriate supports is unknown. The aim of this study was to explore older adults’ experiences accessing social and emotional support during the COVID-19 pandemic in Australia. Method Ten older adults from Western Australia (Australia) aged 68 to 78 years participated in individual semi-structured interviews between December 2020 and January 2021. Responses were investigated using thematic analysis. Results Three key themes emerged: adaptability and self-sufficiency; informal support-seeking; and digital and online technologies. Older adults were adaptable to COVID-19 restrictions; however, some were anxious about reconnecting with their social networks once restrictions had eased. Older adults relied on their informal support networks to maintain their social and emotional wellbeing during lockdown. Digital platforms (e.g., Zoom, social media) enabled older adults to stay connected with others, yet some older people were unable or reluctant to use technology, leaving them vulnerable to social isolation. Conclusions Older adults are resilient to the challenges of COVID-19. Informal supports and digital technologies are important to maintaining social and emotional wellbeing during lockdown. Local governments and community groups may benefit from increased funding to deliver services that promote social connectedness during times of crisis.